THE CONCEPT OF STAGED BUILDING FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE OF PROSPECTIVE SPECIALISTS OF NON-PHILOLOGICAL SPECIALIZATIONIN HIGHER EDUCATIONAL INSTITUTIONS - Nataliia Mykytenko; Volodymyr Sulym (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article deals with the validation of the concept of staged building of a foreign language communicative competence in prospective specialists of non-philological specialization in higher educational institutions.The concept "a foreign language communicative competence in prospective specialists of non-philological specialization" has been defined. It has been established that the methodological-theoretical basis of the concept of staged building of a foreign language communicative competence in prospective specialists of non-philological specialization is framed by the theories of education and learning, methodological, approaches and principles of didactics and methodology; psychological theories of learning and development of individuality; psycholinguistic theories of language teaching; sociolinguistic studies of language usage, linguistic approaches and theories; philosophical theories of development, interrelation and interdependence of phenomena of reality. The main approaches, that enable the concept of staged building of a foreign language communicative competence in prospective specialists of non-philological specialization, are competence-based, communicative, differential ones with orientation to the levels of knowledge of foreign languages established by Council of Europe. The concept of staged building of a foreign language communicative competence in prospective specialists of non-philological specialization is projected on the process of foreign language teaching in higher educational institutions of Ukraine.